Trash as Treasure: learning from an Ash Heap of History in Copan, Honduras - Fash, William L. (2015)
The adage "one open's trash is another person's treasure" rings true for all of us who have happily devoted our professional lives to the study of archaeology. We make our livelihoods—and more importantly we build, dismantle and rebuild cultural histories and archaeological theory—through the concerted study of material culture. The Merriam Webster Dictionary defi nes material culture as the totality of physical objects made by a people for the satisfaction of their needs, especially those articles requisite for their sustenance. The Classic Maya ruins in Copan, Honduras, where we have conducted much archaeological research, provide an excellent example. There, Will (the co-author of this article) uncovered and recovered a large ash-layer midden in the royal residential complex that proved enormously informative. During our time together as director and co-director of the Copan Acropolis Archaeological Project (1988-1996), Will devoted several seasons of field research to the investigation of architectural Group 10L-2, on the south flank of the Acropolis. Evidence indicates that this residential compound had a series of discrete architectural components that were used for different purposes by the ruler, his immediate family and courtiers. These included a large public plaza area, a royal receiving area, residences for the ruler himself, his offspring, and several courtiers, a royal ancestor shrine, and a kitchen area that had been re-purposed from an earlier use as a royal burial ground. Underlying the central part of the residential compound was the midden, which proved vital for understanding not only Will’s site, but the political and economic history of the entire kingdom, a true archaeological "treasure".